Human Nature in Gregory of Nyssa Philosophical Background and Theological Significance - Zachhuber, Johannes (Vigiliae Christianae, Supplements, 2000)
This study in the thought of Gregory of Nyssa seeks to demonstrate in what sense and to what extent the philosophical notion of universal human nature functions as the systematic backbone of this church father's theology.; Readership: All those interested in patristics, ancient philosophy, philosophical theology, the history of Christian thought, the culture of late antiquity; theologians, historians.